(untitled) (Journal of the College of Basic Education, 2022)
The research study urbanization of the city of Baghdad by shedding Aldualy Ocean and the urban fabric and Thdedmrahal evolution morphological city of Baghdad, and the impact of urban growth of the city of Baghdad on its territory agricultural and risk creep residential use on agricultural land or arable leaving traces many negative comes in the forefront of low production agricultural and wide Tadmarmesahat of arable land as well as environmental degradation and the high levels of pollution and low efficiency of functional public services and the infrastructure and the lack of many residential areas, especially randomized them to these services.